ANALISIS PENERAPAN MODEL PEMBELAJARAN KONVENSIONAL DENGAN BERBASIS MEDIA DIGITAL PADA PEMBELAJARAN IPAS DI SD NEGERI SEMPOL 2 - Tasya Zaskia Putri; Aji Husein Priambodo; Oksanko Rahyu Mulyahya; Muhammad Imaduddin; Arif Mahya Fanny (STKIP Subang, 2026)
This study aims to analyze the implementation of conventional learning models and digital media-based learning in IPAS learning at SD Negeri Sempol 2. The conventional learning model is still used because it can foster students’ discipline and responsibility. The implementation of this model is carried out through lectures and direct delivery of material by the teacher. However, this method makes students passive because the learning process is teacher centered. Meanwhile, digital media-based learning is implemented through the use smart TVs, projectors, and learning videos, which make the learning process more enjoyable and encourage students to be more active in class. In addition, local wisdom-based interview projects are assigned to students as an effort to enhance their creativity and contextual understanding. Data collection was conducted through direct interviews with the teacher. The results of the study show that the conventional learning model can foster students’ discipline and politeness. Meanwhile, digital media-based learning supports the improvement of students’ activeness and creativity. Therefore, combining these two learning models can be an effective solution to improve students’ learning outcomes in IPAS.